2012
DOI: 10.1124/jpet.112.192930
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis ofN-Acetylcysteine Treatment for Acetaminophen Overdose Using a Systems Model of Drug-Induced Liver Injury

Abstract: N-acetylcysteine (NAC) is the treatment of choice for acetaminophen poisoning; standard 72-h oral or 21-h intravenous protocols are most frequently used. There is controversy regarding which protocol is optimal and whether the full treatment course is always necessary. It would be challenging to address these questions in a clinical trial. We used DILIsym, a mechanistic simulation of drug-induced liver injury, to investigate optimal NAC treatment after a single acetaminophen overdose for an average patient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 44 publications
1
65
0
3
Order By: Relevance
“…NAC, a precursor of GSH that causes NAPQI detoxification, has been shown to produce remarkable effects against APAP-induced hepatotoxicity in rodents and humans (22,30,31). In the present study, NAC demonstrated such preventive effects against APAP-induced cell injury in NCP-cultured HepG2 cells but did not exhibit any effects on cell injury in the conventionallycultured HepG2 cells.…”
Section: Discussionmentioning
confidence: 51%
“…NAC, a precursor of GSH that causes NAPQI detoxification, has been shown to produce remarkable effects against APAP-induced hepatotoxicity in rodents and humans (22,30,31). In the present study, NAC demonstrated such preventive effects against APAP-induced cell injury in NCP-cultured HepG2 cells but did not exhibit any effects on cell injury in the conventionallycultured HepG2 cells.…”
Section: Discussionmentioning
confidence: 51%
“…DILIsym® describes the intrahepatic accumulation of these toxic bile acids as well as the concentrations in the gallbladder, portal blood, gut lumen, and systemic blood. Concentrations of bile acid transporter inhibitors are modeled using a physiologically-based pharmacokinetic model (PBPK) described in depth in previous papers (Howell et al, 2012; Woodhead et al, 2012). The bile acid concentrations are linked to ATP decline as described below; the effect of ATP decline on eventual hepatocyte necrosis is described by a model of the hepatocyte life cycle also described in previous papers (Howell et al, 2012; Woodhead et al, 2012; Shoda et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…DILIsym® is a multi-scale mechanistic model incorporating numerous functions of the liver and disruptions of the function with the goal of predicting the DILI potential of drugs at various stages in the development process (Howell et al, 2012, 2014; Woodhead et al, 2012; Shoda et al, 2014). Previously, we have constructed and validated a model of bile acid homeostasis and transporter inhibition within DILIsym® (Woodhead et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The basic DILIsym PBPK model framework consists of a compartmental model of the body with compartments for blood, gut, liver, muscle, and other tissues and has been described in previous publications 5, 8, 15. Because BAL30072 has been shown to be a substrate of organic anion transporter (OAT)1, OAT3, organic anion‐transporting polypeptide (OATP)1B1, and OATP1B3,4 the saturable liver uptake model was used for BAL30072.…”
Section: Methodsmentioning
confidence: 99%